Drawing as Instrument, Drawings as Evidence: Capturing Mental Processes with Pencil and Paper. Issue 3 (13th June 2016) - Puglionesi, Alicia
Abstract : Researchers in the mind sciences often look to the production and analysis of drawings to reveal the mental processes of their subjects. This essay presents three episodes that trace the emergence of drawing as an instrumental practice in the study of the mind. Between 1880 and 1930, drawings gained currency as a form of scientific evidence – as stable, reproducible signals from a hidden interior. I begin with the use of drawings as data in the child study movement, move to the telepathic transmission of drawings in psychical research and conclude with the development of drawing as an experimental and diagnostic tool for studying neurological impairment. Despite significant shifts in the theoretical and disciplinary organisation of the mind sciences in the early twentieth century, researchers attempted to stabilise the use of subject-generated drawings as evidence by controlling the contexts in which drawings were produced and reproduced, and crafting subjects whose interiority could be effectively circumscribed. While movements such as psychoanalysis and art therapy would embrace the narrative interpretation of patient art, neuropsychology continued to utilise drawings as material traces of cognitive functions.